The impact of children’s enrollment restrictions on household consumption: evidence from the migrant population - Xie, Jianfeng; Guo, Meiyi; Li, Chengyu (Frontiers in Public Health, 2025)
IntroductionThis study explores the economic effects of school enrollment restrictions derived from the household registration system on the consumption behavior of migrant families. With intensified globalization and increasing population mobility, enrollment restrictions—arising from factors such as migrant status, policies, or resource allocation—have become a critical issue at the regional level. The effect of education policies on migrant children’s enrollment restrictions and household consumption willingness remains a subject of debate in the academic community.MethodsUsing 2014–2017 household microdata of the migrant population, this study constructs an index of enrollment threshold for migrant children based on policy documents of each city. A microeconometric model is built to estimate and examine the economic effects of education policies for migrant children on household consumption levels.ResultsThe results indicate that a decline in the school enrollment threshold can significantly improve the household consumption of migrant families. The findings pass several robustness tests and endogeneity tests. Furthermore, the impact of the schooling threshold on household consumption is more profound among migrant households with characteristics such as being an only child, intra-provincial mobility, and a willingness to settle down.DiscussionThe conclusion highlights that regional educational equity can effectively promote the consumption willingness of the migrant population and enhance socioeconomic inclusivity. The study provides important policy recommendations for safeguarding and supporting the well-being of migrant families.